Hubungan Kadar Debu Lingkungan Kerja, Masa Kerja dan Penggunaan Alat Pelindung Diri dengan Gejala Subyektif Pneumokoniosis Pada Pekerja Industri Batu Bata di Desa Sitimulyo, Piyungan, Bantul - Okvendri Abrihari; Agus Suwarni; Sigid Sudaryanto (Poltekkes Kemenkes Yogyakarta, 2014)
One of negative impacts from industrial activity is pollution, such as the air one caused by indus-trial processing dust. The dust pollution particle if inhalated into respiratory tract can cause occu-pational diseases, i.e. pneumoconiosis, for the affected workers. The objective of the study was to determine the relationship betwen workplace dust levels, period of employment and the wear-ing of personal protective equipment, and subjective symptoms of pneumoconiosis among brick-making industry workers in Sitimulyo Village of Piyungan, Bantul, by conducting a cross sectional approached survey. There were 42 worker respondents from 10 brick industries who were inter-viewed for obtaining the data of employment period and symptoms of pneumoconiosis, and were also observed for gaining information about masker wearing, while the dust concentration were measured by using Staplex HVAS instrument. The results showed that half of the industries were exposed by dust level, higher than the threshold limit value; 61,90 % of the workers were aged more than 20 years old; 38,10 % of the workers did not wear mask; and 59,52 % of the workers were experiencing the subjective symptoms of the disease. Statistical analysis by using spear-man correlation test at 95 % degree of confidence, found that factors which were correlated with pneumoconiosis was period of employment (p = 0,008) and wearing mask (p = 0,010). However, workplace dust level was not found to be related with the disease (p = 0,097). It is advised for the workers to highly aware in wearing mask habitually as one of the preventive measures.